Information modelling and knowledge bases XVII - Kiyoki, Yasushi (Frontiers in artificial intelligence and applications, 2006)
Provide research communities in information modelling and knowledge bases with scientific results and experiences achieved by using innovative methodologies in computer science and other disciplines related to linguistics, philosophy, and psychology.